Effects of processing and storage on Pediococcus pentosaceus SB83 in vaginal formulations: lyophilized powder and tablets - Borges, Sandra (2014)
Vaginal probiotics have an important role in preventing the colonization of the vagina by pathogens. This study aimed to investigate different formulations with Pediococcus pentosaceus SB83 (lyophilized powder and tablets with and without retarding polymer) in order to verify its stability and antilisterial activity after manufacture and during storage. The bacteriocinogenic activity of P. pentosaceus SB83 against Listeria monocytogenes was evaluated in simulated vaginal fluid. Suspension of Pediococcus pentosaceus SB83 reduced the pathogen only after 2 h and the lyophilized bacteria after 24 h of contact, and, in the tablets, P. pentosaceus SB83 lost the antimicrobial activity. The pH of simulated vaginal fluid decreased for all the tested conditions. As lyophilized powder demonstrated better results concerning antimicrobial activity, this formulation was selected to evaluate the antilisterial activity during the 12 months of storage. During storage at room temperature, lyophilized bacteria totally inhibited the pathogen only until one month of storage. At 4 degrees C, P. pentosaceus SB83 showed antimicrobial activity during all the time of storage investigated. Therefore, the better formulation of P. pentosaceus SB83 is the lyophilized powder stored at 4 degrees C, which may be administered intravaginally as a washing solution.